2024
DOI: 10.1021/acs.estlett.4c00333
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Decreases with the Decay of Environmentally Persistent Free Radicals in Particulate Matter from Incomplete Solid Fuel Burning

Anyuan Cheng,
Xiu Chen,
Di Wu
et al.

Abstract: Environmentally persistent free radicals (EPFRs) have been linked to the generation of reactive oxygen species (ROS) and adverse health effects. However, there remains a knowledge gap regarding the dynamic changes in reactivity and toxicity during the decay process of EPFRs emitted from incomplete solid fuel burning, which are identified as a primary source of EPFRs. Here, we report the decay behavior of EPFRs in particulate matter (PM) emitted from typical solid fuel burning and the associated ROS generation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
(144 reference statements)
0
0
0
Order By: Relevance
“…Our finding revealed that the differences in average densities of EPFRs among different fuels were insignificant ( p > 0.05), the values in the coal and raw biomass emissions were almost equal, at 5.8 × 10 16 spins/g PM 2.5 , and that in the biomass pellet emission was 5.5 ± 3.9 × 10 16 spins/g PM 2.5 . The mass concentration of the EPFRs in the PM 2.5 from residential fuel combustion in this study was likely lower than those (10 14 to 10 18 spins/g PM 2.5 ) reported in some studies. Besides different fuels and burning conditions, changes in EPFRs during the aging process of particles may also contribute to the observed differences among different studies …”
Section: Resultscontrasting
confidence: 61%
“…Our finding revealed that the differences in average densities of EPFRs among different fuels were insignificant ( p > 0.05), the values in the coal and raw biomass emissions were almost equal, at 5.8 × 10 16 spins/g PM 2.5 , and that in the biomass pellet emission was 5.5 ± 3.9 × 10 16 spins/g PM 2.5 . The mass concentration of the EPFRs in the PM 2.5 from residential fuel combustion in this study was likely lower than those (10 14 to 10 18 spins/g PM 2.5 ) reported in some studies. Besides different fuels and burning conditions, changes in EPFRs during the aging process of particles may also contribute to the observed differences among different studies …”
Section: Resultscontrasting
confidence: 61%
“…Our results imply that exposure to EPFRs and inhalation and respiratory deposition of PM may cause oxidative stress and adverse health effects. A very recent study has observed a positive correlation between cytotoxicity and EPFR concentration . Another recent study by Yang et al (2024) showed that PM oxidative potential in Fairbanks is comparable to that in Atlanta and Los Angeles .…”
Section: Discussionmentioning
confidence: 94%